EMBEDDED SOLUTION FOR TRAFFIC SIGNAL CONTROLLER AND APPLICATION TO TRAFFIC STATE IN VIET NAM - Trung, Nguyễn Hữu; Anh, Nguyễn Thuý (Vietnam Journal of Science and Technology, 2012)
SUMMARY Traffic signal controller is playing more and more important roles in modern management and control of urban traffic, especially in complicated, particular traffic of Viet Nam. Growing numbers of road users and the limited resources provided by current infrastructures lead to the fact that traffic controllers have capability to perform advanced traffic schemes. This paper presents an advanced traffic signal controller based on embedded technology. The proposed model architecture, traffic control strategies of the advanced traffic signal controller is firstly introduced in detail, then application cases in practice of Viet Nam is discussed